U-Turn Analysis on Road Performance by Dr. Ir. H. Soekarno Merr (Case Study: West and East Side U-Turn) - Theresia MCA; Dewi Kusumaningrum; Ratih Sekartadji; Dimas Agung (Journal of Civil Engineering, Planning and Design, 2022)
Traffic is a system consisting of several key elements or a headway system. In the median plan, it also has a center opening or U-Turn, but the U-Turn facility does not completely solve these problems and conflicts because the turning vehicle itself does not completely solve them. This is the result of turning in the same direction as vehicles approaching or stopping in high and low-speed lanes. Some vehicles are unable to make smooth U-Turns, causing delays for both traffic directions or vice versa. This study aims to determine the traffic performance and performance of the U-Turn facility on Jl. Dr. Ir. Soekarno in the City of Surabaya using the MKJI methodology, 1997. From the results of this study, the peak hours for the south direction (A) are at 16.45-17.45, volume 3480. 6 vehicles per hour, DS (Degree of saturation)  0.73 with service level C, and south to north (B) at 16:45-17.45, volume 3394. 7 vehicles per hour DS 1.07 means the level of service indicates a long queue. The U-Turn movement has the highest volume at 16.45-17.45, with a volume of 656.8 pcu/hour and an intensity ratio greater than 1.0, indicating a vehicle queue.